Spatial distribution of microplastics in sandy beach and inshore-offshore sediments of the southern Caspian Sea. (August 2021) - Manbohi, Ahmad; Mehdinia, Ali; Rahnama, Reza; Dehbandi, Reza; Hamzehpour, Ali
Abstract: The occurrence of microplastics (MPs) in nearshore zones of the southern Caspian coasts is well documented; however, no data are available on MP occurrence in offshore sediments. In this study, six sandy beach stations and 18 inshore-offshore stations (six transects) were surveyed. MPs were detected in all sediment samples. The mean abundances of MPs in the beach and inshore-offshore stations were 196.67 ± 11.58 and 103.15 ± 7.21 MPs/kg, respectively. Fibers constituted the most common shape of MPs. Polystyrene (PS) and polyethylene terephthalate (PET) were the major polymer types found in the beach and inshore-offshore sediments, respectively. In most transects, negative MP gradients were observed from nearshore to offshore, which showed that coastal fishing, tourism, and rivers were the main sources of MPs in this area. These results will improve our understanding on MPs pollution in the marine ecosystem. We recommend further MP studies in different parts of the Caspian Sea to develop appropriate management programs. Graphical abstract: Unlabelled Image Highlights: Spatial distribution of MPs in beach and inshore-offshore sediments was explored. MPs were detected in the entire beach, inshore and offshore sediment samples. Negative gradients of MPs from nearshore to offshore sediments were observed. Fibers were dominant in both media. PS and PET were dominant in beach and inshore-offshore sediments, respectively.